Shielding free movement? Reciprocity in welfare institutions and opposition to EU labour immigration - Mårtensson, M; Österman, M; Palme, J; Ruhs, M (Taylor & Francis (Routledge), 2021)
Public attitudes towards the free movement of workers in the European Union vary substantially between countries and individuals. This paper adds to the small but growing research literature on this issue by analysing the role of national welfare institutions. We investigate the relationship between the degree of ‘institutional reciprocity’ in national systems of social protection and attitudes to EU labour immigration across 12 European countries. We do not find evidence of an effect of institutional reciprocity on opposition to EU labour immigration among the public at large. However, institutional reciprocity appears to matter for economically vulnerable groups. We identify an interaction effect indicating that higher degrees of institutional reciprocity in national social protection systems, and in unemployment insurance systems specifically, are associated with lower levels of opposition to EU labour immigration among unemployed people. Hence, reciprocity in welfare state institutions appears to shield free movement from opposition, at least among vulnerable groups.